Ada Apa di Balik âPincalangâ Idris Pasaribu, Sebuah Kritikan - Harahap, Abdul Rahim (Universitas Islam Sumatera Utara, 2013)
ABSTRACTThis criticism aims to see how extent the structural reinforcement novel âPincalangâ by Idris Pasaribu terms of themes and forms. The themes will question the existence of man marine (boatpeople) in North Sumatera Sibolga to exploit cultural values and religion. While the shape, justanalyze the dominant elements in the novel. And then vote as strengths and weaknesses. Themethod used is the structure and descriptive methods. Both methods are used to see âwhatâ andâhowâ the themes and forms of it in the novel.The research reveals that in fact of Presidential decree to launch a boat loan in addition failing toimprove the welfare of fishermen in general, can also threaten boat human life. Proven decree onlybenefits the employers and authorities, while the lives of poor fishermen and boat people remainpoor. And families victimized Amat (punished to 7 years in prison) despite his determination aftergetting out from prison are to continue living as the sea with the truth and trying to save the humannature of any land disturbance.The strength of this novel, apart from the intent is the novelist wants the dignity of boat peopletoday, as well as conduct suspension at the beginning of the story, making in interest andmemorable. But the weakness is the novelist did curbs on character actors that seem like reportageonly. The authors concluded that the implementation of the presidential decree boat loans to thefishermen in the west coast of northern Sumatra province Sibolga need to review again.Keyword : Appreciation, Novel, Critical